Analysis of Factors Influencing Anxiety in Facing Labor Period in Pregnant Women Third Trimester at Elpi Al-Azis Hospital Labuhanbatu - Hasibuan, Siti Tuahta Pertiwi; Asriwati; Nasution, Ramadhani Syafitri (International Journal of Educational and Psychological Sciences, 2024)
Anxiety or anxiety of pregnant women who will face the process of labor is one of the problems of emotional disorders that are often encountered. Preliminary data from researchers showed that the baby birth rate reached 185 births in February-April 2024. There were 721 registered pregnant women doing Antenatal Care (ANC). Objective research to analyze the factors that influence anxiety facing labor in third trimester pregnant women at Elpi Al-Azis Labuhanbatu Hospital. The research design used Analytical Survey method with Cross Sectional approach. The population in this study were all pregnant women pregnant women at Elpi Al-Azis Labuhanbatu Hospital, namely 90 people who were all made into research samples with accidental sampling techniques. Data analysis using univariate analysis, bivariate with chi-square test and multivariate with logistic regression. The results of logistic regression research showed that there was an effect of maternal pregnancy examination history p = 0.004 and husband support p = 0.000. While the dominant factor influencing anxiety facing labor labor period in third trimester pregnant women, namely husband support p = 0.001 with Exp(B) 241.660. Conclusion the conclusion of this study is that there is an effect of maternal age, gravida, history of prenatal check-ups and husband support. husband. The dominant factor, namely husband's support, influences anxiety in facing labor in third trimester pregnant women at Elpi Al-Azis Labuhanbatu Hospital. It is recommended that Elpi Al-Azis Labuhanbatu Hospital should conduct counseling for pregnant women about the level of anxiety in pregnant women, the impact of anxiety, and how to prevent it. anxiety in pregnant women, the impact of anxiety, and how to prevent it. The need to educate about the problem of anxiety anxiety problems in third trimester pregnant women when conducting Antenatal Care (ANC).